STUDENT LEARNING EVALUATION SYSTEM IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SENIOR HIGH SCHOOL 1 LEMBAH MELINTANG - Marzuki; Dina Septiana, Yulda; Hidayat, Taufik; Lutfiyani (Mandeh : Jurnal Pendidikan Islam, 2024)
This study aims to determine the implementation of student learning evaluation in Islamic Religious Education subjects at Lembah Melintang 1 Senior High School and its supporting and inhibiting factors. This study uses a field research approach with key informants in the form of Islamic Religious Education teachers and principals, as well as student support informants. Data collection techniques used include interviews, observation, and documentation. The results of the study indicate that evaluation at Lembah Melintang 1 Senior High School is carried out using general methods also used in other schools, including daily tests, mid-term exams, and final exams, as well as Core Competency assessments (which include spiritual, social, knowledge, and skills aspects). Supporting factors for evaluation include the availability of the 2023 Curriculum assessment program from the school, while inhibiting factors include low student understanding and interest in learning, environmental and social media influences, mobile phone use, and limited learning materials. This study concludes that the evaluation has been running well, but efforts are needed to increase effectiveness through the development of assessment instruments and attention to inhibiting factors.